Comorbidity and Therapeutic Approaches in Patients with Necrobiosis Lipoidica - Erfurt-Berge, Cornelia; Heusinger, Veronika; Reinboldt-Jockenhöfer, Finja; Dissemond, Joachim; Renner, Regina (Dermatology, 2021)
Background: Necrobiosis lipoidica (NL) is a rare granulomatous disorder of unknown aetiology. Randomized controlled studies are not available due to it being an orphan disease. Objectives: We evaluated patients in 2 dermatological centres to cluster data about epidemiology, the therapeutic approaches for NL, and their efficacy. Materials and Methods: Comorbidity and the efficacy of the applied treatment was assessed for 98 patients. Results: We identified 54% of patients with concomitant diabetes and 19% with thyroidal disorders. Topical steroids (85.7%) were predominantly used followed by calcineurin inhibitors (31%) and phototherapy (41.8%). Systemically, fumaric acid esters were more frequently applied (26.8%) than steroids (24.4%) and dapsone (24.4%). Steroids, compression therapy, calcineurin inhibitors, phototherapy, fumaric acid esters, and dapsone showed remarkable efficacy. Conclusion: Therapeutic options were chosen individually in accordance with the severity of NL and presence of ulceration. Topical calcineurin inhibitors, systemic application of fumaric acid esters, and dapsone represent effective alternatives to the use of steroids.
CRIS-Team Scopus Importer:2021-04-19